(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gingival diseases are prevalent in both children and adolescents. These diseases may or may not be associated with plaques, maybe familial in some cases, or may coexist with systemic illness. However, gingiva and periodontium receive scant attention as the primary dentition does not last for a considerable duration. As gingival diseases result in the marked breakdown of periodontal tissue, and premature tooth loss affecting the nutrition and global development of a child/adolescent, precise identification and management of gingival diseases is of paramount importance. This article comprehensively discusses the nature, spectrum, and management of gingival diseases.